Pengembangan Media Ajar Interaktif dalam Meningkatkan Hasil Belajar Matematika Kelas III SDN 2 Jonggrangan - Rifqi Asiah; Dihan Nanda Hamidah; Saudah Khodijah; Aprilia Kinantika Sari; Putri Zudhah Ferryka (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Education is a learning process that takes place in the form of teaching and learning activities, where in these activities there is interaction between educators and students. However, in reality, learning is still dominated by educator-centered lecture methods, so that two-way interaction and active involvement of students are not optimal. The use of Canva-based interactive learning media is one of the alternatives to overcome this problem. This research uses the Research and Development (R&D) method which aims to produce a product in the form of canva-based interactive teaching media and test the feasibility and effectiveness of improving student learning outcomes in grade III Mathematics subjects. According to validation tests involving material experts, media experts, and small group trials, it showed a feasibility percentage of 92.66% with a very feasible category. Based on the results of the pre-test, it was obtained that students who achieved 55% completeness while the post-test results were obtained that students who achieved completeness were 85%. This shows that there is an increase in completeness by 30%. Thus, the development of Canva-based interactive teaching media can be used as an innovative solution in improving learning outcomes in mathematics subjects.